Comparative properties characteristics of the various pastes based on calcium hydroxide - M. M. Shubitidze; A. B. Adzhieva; N. A. Dadashov; M. T. Bagisheva; K. N. Shcherba; S. M. Solimanov; S. A. Nazhmudinov (LLC "Endo Press", 2020)
Calcium hydroxide is widely used as a interappointment root canal filling material due to its favorable alkaline effect. It is assumed that the action occurs from the diffusion of hydroxyl ions through the apical foramen. The aim of this article was to review studies of the various properties of pure calcium hydroxide, as well as its commercial analogues.